2008
DOI: 10.1080/15459620801894386
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Tolerance in a Full-Body Safety Harness, and a Prototype Harness Accessory

Abstract: Workers wearing full-body safety harnesses are at risk for suspension trauma if they are not rescued in 5 to 30 min after a successfully arrested fall. Suspension trauma, which may be fatal, occurs when a person's legs are immobile in a vertical posture, leading to the pooling of blood in the legs, pelvis, and abdomen, and the reduction of return blood flow to the heart and brain. To measure suspension tolerance time, 22 men and 18 women with construction experience were suspended from the chest D-ring (CHEST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Literature has reported that body weight (Turner et al, 2008) and stature (Seddon, 2002) were predictors for suspension tolerance. This study contributes additional information to the literature on the impact of harness fit on suspension tolerance.…”
Section: Discussion Factors Associated With Suspension Tolerance Timementioning
confidence: 99%
“…Literature has reported that body weight (Turner et al, 2008) and stature (Seddon, 2002) were predictors for suspension tolerance. This study contributes additional information to the literature on the impact of harness fit on suspension tolerance.…”
Section: Discussion Factors Associated With Suspension Tolerance Timementioning
confidence: 99%
“…Since the completion of this literature review, work has been published by Turner et al that examined the use of a passively deploying mechanism to elevate the legs during harness suspension 19. Using this mechanism, suspension was tolerated for a mean of 58 min without any subjects experiencing presyncope, all withdrawals were due to discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In study I, the harness was tested for fit while participants were both standing and suspended. A pass or fail rating was assigned based on four criteria that are in use in the harness manufacturing industry to minimise any potential biomechanical stress and suspension trauma (Brinkley 1988, Turner et al 2008. The pass criteria were that: (1) the harness back D-ring was positioned between the inferior and superior borders of the scapula while the participant was standing; (2) the suspension angle had to be equal to or less than 358 during the suspension condition; (3) the chest strap should not make contact with the neck while the participant was suspended; (4) the centre of gravity (COG) of the body had to be behind the hip rings during the suspension condition.…”
Section: Independent Variablesmentioning
confidence: 99%